Profile and management of pediatric brain tumors: A single-center experience - Nhu Hiep Pham; Huu Son Nguyen; Kiem Hao Tran; Nguyen Cuong Pham (GarVal Editorial Ltda., 2021)
Context: Pediatric brain tumors are the most common solid tumors and the leading cause of death among children worldwide. Although there are some published studies from many countries regarding the pathological model of pediatric brain tumors, comprehensive clinical pathology studies conducted at Vietnam are still lacking. Aims: To explore the clinical and histopathological features of pediatric brain tumors at a central hospital in Vietnam. Methods: This study used a retrospective epidemiological approach. Children aged <17 years were selected according to their profiles registered in our department during 2016-2020 when they were diagnosed with primary brain tumors. Data of patients' age, sex, clinical features, and histology were collected. The 2016 World Health Organization classification of tumors was adopted. Results: A total of 34 patients with brain tumors were identified, with a males/females ratio of 2.8/1. Patients' age ranged from 3 months to 16 years, with a median age of 6 years. The most common presentation of brain tumor in our series was headache (47.1%). According to the location of involvement, 51.5% of the tumors were in supratentorial region. Moreover, astrocytes (55.9%) were the most common type of pediatric brain tumors. Surgery was the main treatment, and chemotherapy was administered to 14.7% of patients. Conclusions: This study addresses the issue of sensitivity but not that of specificity of clinical features to the presence of an underlying brain tumor. Histopathology analysis is necessary to develop further treatment after neurosurgery.